Aconitine and its derivatives: bioactivities, structure-activity relationships and preliminary molecular mechanisms - Zhao, Pengyu; Tian, Ye; Geng, Yuefei; Zeng, Chenjuan; Ma, Xiuying; Kang, Jie; Lu, Lin; Zhang, Xin; Tang, Bo; Geng, Funeng (Frontiers in Chemistry, 2024)
Aconitine (AC), which is the primary bioactive diterpene alkaloid derived from Aconitum L plants, have attracted considerable interest due to its unique structural feature. Additionally, AC demonstrates a range of biological activities, such as its ability to enhance cardiac function, inhibit tumor growth, reduce inflammation, and provide analgesic effects. However, the structure-activity relationships of AC are remain unclear. A clear understanding of these relationships is indeed critical in developing effective biomedical applications with AC. In line with these challenges, this paper summarized the structural characteristics of AC and relevant functional and bioactive properties and the structure-activity relationships presented in biomedical applications. The primary temporal scope of this review was established as the period spanning from 2010 to 2023. Subsequently, the objective of this review was to provide a comprehensive understanding of the specific action mechanism of AC, while also exploring potential novel applications of AC derivatives in the biomedical field, drawing upon their structural characteristics. In conclusion, this review has provided a comprehensive analysis of the challenges and prospects associated with AC in the elucidation of structure-bioactivity relationships. Furthermore, the importance of exploring modern biotechnology approaches to enhance the potential biomedical applications of AC has been emphasized.